Pixel-based graphical password scheme password from digital image file - Mohd Sidek Fadzil Mohd Yunus; Mohd. Afizi Mohd. Shukran; Muhammad Naim Abdullah
This book's intention is mainly to briefly present a dynamic analysis for developing a model of graphical password scheme that solving current graphical password issues.